Black enough stories of being young & black in America - Zoboi, Ibi; Watson, Renée; Johnson, Varian 1977-; Henderson, Lee 1974-; Giles, Lamar; Magoon, Kekla 1980-; Reynolds, Jason 1983-; Colbert, Brandy; Onyebuchi, Tochi; Tamani, Liara; Coles, Jay; Williams-Garcia, Rita 1957-; et al. (Balzer + Bray, an imprint of HarperCollinsPublishers, 2019)
Black is ... sisters navigating their relationship at summer camp in Portland, Oregon, as written by Renée Watson. Black is ... three friends walking back from the community pool talking about nothing and everything, in a story by Jason Reynolds. Black is ... Nic Stone's high-class beauty dating a boy her momma would never approve of. Black is ... two girls kissing in Justina Ireland's story set in Maryland. Black is urban and rural, wealthy and poor, mixed race, immigrants, and more--because there are countless ways to be Black enough. A collection of short stories explore what it is like to be young and black, centering on the experiences of black teenagers and emphasizing that one person's experiences, reality, and personal identity are different than someone else